The Kalanchoë genome provides insights into convergent evolution and building blocks of crassulacean acid metabolism. Issue 1 (December 2017) - Yang, Xiaohan; Hu, Rongbin; Yin, Hengfu; Jenkins, Jerry; Shu, Shengqiang; Tang, Haibao; Liu, Degao; Weighill, Deborah; Cheol Yim, Won; Ha, Jungmin; Heyduk, Karolina; Goodstein, David; et al.
Abstract Crassulacean acid metabolism (CAM) is a water-use efficient adaptation of photosynthesis that has evolved independently many times in diverse lineages of flowering plants. We hypothesize that convergent evolution of protein sequence and temporal gene expression underpins the independent emergences of CAM from C3 photosynthesis. To test this hypothesis, we generate a de novo genome assembly and genome-wide transcript expression data forKalanchoë fedtschenkoi, an obligate CAM species within the core eudicots with a relatively small genome ( 260 Mb). Our comparative analyses identify signatures of convergence in protein sequence and re-scheduling of diel transcript expression of genes involved in nocturnal CO2 fixation, stomatal movement, heat tolerance, circadian clock, and carbohydrate metabolism inK. fedtschenkoi and other CAM species in comparison with non-CAM species. These findings provide new insights into molecular convergence and building blocks of CAM and will facilitate CAM-into-C3 photosynthesis engineering to enhance water-use efficiency in crops. Crassulacean acid metabolism (CAM) is a metabolic adaptation of photosynthesis that enhances water use efficiency. Here, via genomic analysis ofKalanchoë, the authors provide evidence for convergent evolution of protein sequence and temporal gene expression underpinning the multiple independent emergences of CAM.